A Comparative Study of Electronic-Based Sexual Violence: Maqashid Shari'ah Perspective on Indonesia's Law No. 12 of 2022 and Malaysia's Legal Framework - Luciana Anggraeni; Zainab Az Zahro; Siti Syahirah Safinee (IAIN KUDUS, 2026)
Non-Indexed Publication